2017
DOI: 10.1073/pnas.1617698114
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disadvantage, gestational immune activity, and neurodevelopment in early childhood

Abstract: Children raised in economically disadvantaged households face increased risks of poor health in adulthood, suggesting that inequalities in health have early origins. From the child's perspective, exposure to economic hardship may begin as early as conception, potentially via maternal neuroendocrine-immune responses to prenatal stressors, which adversely impact neurodevelopment. Here we investigate whether socioeconomic disadvantage is associated with gestational immune activity and whether such activity is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 57 publications
4
78
0
1
Order By: Relevance
“…Two studies have shown that across several cytokines, higher mid-gestational levels are associated with an increased risk of autism and autism with intellectual disability or developmental delay relative to controls (Jones et al, 2017; Abdallah et al, 2013). In another recent study utilizing a historical cohort ascertained between 1959 and 1966, investigators found lower IL- 8 assayed from maternal serum obtained in early in the third trimester of pregnancy to be related to a higher risk of physician assessed neurological abnormalities at 4 months and 1 year of age (Gilman et al, 2017). Generally, it is difficult to compare our findings to these studies since the populations and outcomes being assessed across these studies differ materially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have shown that across several cytokines, higher mid-gestational levels are associated with an increased risk of autism and autism with intellectual disability or developmental delay relative to controls (Jones et al, 2017; Abdallah et al, 2013). In another recent study utilizing a historical cohort ascertained between 1959 and 1966, investigators found lower IL- 8 assayed from maternal serum obtained in early in the third trimester of pregnancy to be related to a higher risk of physician assessed neurological abnormalities at 4 months and 1 year of age (Gilman et al, 2017). Generally, it is difficult to compare our findings to these studies since the populations and outcomes being assessed across these studies differ materially.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, developmental neuropsychiatric conditions, such as schizophrenia in adulthood and autism in childhood, have been linked with elevated gestational levels of cytokines and chemokines (Brown et al, 2004; Jones et al, 2017). Further, lower gestational levels of 1L-8 have been associated with physician assessed neurological abnormalities at 1 year of age (Gilman et al, 2017), and at least one study has shown that umbilical cord blood concentrations of inflammatory cytokines are associated with child cognitive intellectual abilities (i.e., intellectual quotient (IQ)) (von Ehrenstein et al, 2012). These studies highlight the association between gestational immune activity and broad-based cognitive abilities, but less is known regarding the extent to which gestational immune activity relates to other domains of functioning, such as those related to executive functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies among preterm infants that assessed immune markers (ie, before the emergence of behavioural and cognitive impairments) suggest that low‐grade inflammation adversely impacts child brain development . However, few studies examined this association in term infants . Moreover, we do not yet know which markers of immune activity are most important for brain development, nor whether higher or lower levels of immune markers are associated with better or worse developmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Longitudinal Investigation of Fertility and the Environment (LIFE) study, a mixture of endocrine‐disrupting chemicals were assessed in relation to a spectrum of reproductive outcomes, including semen quality and couples' time‐to‐pregnancy. Another example is in assessing parental demographic and socioeconomic factors and neonatal outcomes, both through and around maternal lifestyle and immune activity . Similar examples abound in the social sciences, public health, and clinical medicine.…”
Section: Introductionmentioning
confidence: 98%